Identifikasi Nilai Tambah dan Risiko Rantai Pasokaktor IKM Kerupuk Ikan Berdaya Saing di Kecamatan Tulangan Sidoarjo - Syah, Zahir; Purwanto, Budi; Cahyadi, Eko Ruddy (Jurnal Aplikasi Manajemen, 2016)
The impact of decline in production IKM is decrease the competitiveness. That is the emergence of the need to identify the added value, risk supply chain and competitiveness of SMEs Fish Crackers. Identification of the value added by Hayami method the result showed thatthe value added amounted Rp 5522 per kg with a percentage of 67.23 percent. The risk identification using FMEA method showedthe highest risk index of delivery risk and supply risk, and to see the effect of the risk, the value added to competitiveness used SmartPLS method. The result showed that the variable MRP has a significant effect to variable R, variable MRP against variable K did not have a significant effect to the variable K, variable R did not affect to variable NT. Variable R has a significant effect tovariable DS, Variable NT has a significant effect to the DS.